Implementation of the Guided Inquiry Learning Model Through Experiments to Improve Conceptual Understanding and Critical Thinking - Zaenuri, Muhammad; Saptono, Sigit; Subali, Bambang (Unnes Science Education Journal, 2025)
This research aims to analyze the effect of the guided inquiry learning model through experiments on the improvement of students’ conceptual understanding and critical thinking skills, as well as its correlation with dynamic electricity material. This research is an experimental quantitative study with a pretest-posttest control design. The research sample consists of students from class 9D and 9E at SMP Negeri 1 Winong Pati. The Cronbach Alpha reliability test yielded a value range of 0.60 ≤rxy≤ 0.80, which falls into the high category. The feasibility test of the instrument material has been validated by expert validators with an average score of 4.60, falling into the very good category. The analysis results show that the N-gain test results are in the range of 0.3-0.7 with a moderate category. The results of the paired samples t-test with a sig (2-tailed) value of 0.000 < 0.05, Ho is rejected and Ha is accepted. The results of the product moment correlation test obtained a significance value of 0.017 < 0.05. Based on all the criteria of the analysis results, it can be concluded that the guided inquiry learning model through experiments is quite effective and has an impact on improving students’ conceptual understanding and critical thinking skills, and there is a significant correlation between the improvement in conceptual understanding and students’ critical thinking skills.